Leukotriene receptor expression in esophageal squamous cell cancer and non-transformed esophageal epithelium: a matched case control study. Issue 1 (December 2016) - Venerito, M.; Helmke, C.; Jechorek, D.; Wex, T.; Rosania, R.; Antweiler, K.; Weigt, J.; Malfertheiner, P.
Abstract Background Leukotriene B4 (LTB4R and LTB4R2) and cysteinyl leukotriene receptors (CYSLTR1 and CYSLTR2) contribute to malignant cell transformation. We aimed to investigate the expression of LTB4R, LTB4R2, CYSLTR1 and CYSLTR2 in esophageal squamous cell carcinoma and adjacent non-transformed squamous epithelium of the esophagus, as well as in control biopsy samples from esophageal squamous epithelium of patients with functional dyspepsia. Methods Expression of LTB4R, LTB4R2, CYSLTR1 and CYSLTR2 was analyzed by immunohistochemistry (IHC) and quantitative reverse transcription-polymerase chain reaction (qRT-PCR) in biopsy samples of 19 patients with esophageal squamous cell cancer and 9 sex- and age-matched patients with functional dyspepsia. Results LTB4R, LTB4R2, CYSLTR1 and CYSLTR2 were expressed in all biopsy samples. Major findings were: 1) protein levels of all leukotriene receptors were significantly increased in esophageal squamous cell cancer compared to control mucosa (p < 0.05); 2)CYSLTR1 andCYSLTR2 gene expression was decreased in cancer tissue compared to control at 0.26–fold and 0.23–fold respectively; 3) an up-regulation of LTB4R (mRNA and protein expression) and a down-regulation ofCYSLTR2 (mRNA expression) in non-transformed epithelium of cancer patients compared to control (p < 0.05) was observed. Conclusions The expression of leukotriene receptors was deregulated in esophageal squamous cell cancer. Up-regulation ofLTB4R and down-regulation ofCYSLTR2 gene expression may occur already in normal squamous esophageal epithelium of patients with esophageal cancer suggesting a potential role of these receptors in early steps of esophageal carcinogenesis. Larger studies are warranted to confirm these observations.